Recent Publications (Quarterly Journal of Economics, 1938)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 52, Issue 4, August 1938, Pages 718–722, https://doi.org/10.1093/qje/52.4.718 Published: 01 August 1938